CAVERNOUS LYMPHANGIOMA OF THE TONGUE IN AN ADULT: A CASE REPORT - Selin EREN; Ahmet Taylan ÇEBİ; Sabri Cemil İŞLER; Metin Berk KASAPOĞLU; Nihan AKSAKALLI; Çetin KASAPOĞLU (Istanbul University, 2017)
Lymphangioma is a benign hamartomatous lesion caused by congenital malformation of the lymphatic system. This benign tumor is detected most commonly at birth or in early childhood but rarely in adults. On clinical examination, most lymphangiomas contain clear lymph fluid, but some may present as transparent vesicles containing red blood cells due to hemorrhage. In addition, lymphangioma may occur in association with hemangioma. This tumor occurs most commonly in the head and neck area, but rarely in the oral cavity. The dorsum of the tongue is the most common location in the mouth, followed by the lips, buccal mucosa, soft palate, and floor of the mouth. There are various treatment approaches for lymphangioma, but surgical excision is the preferred method. We present a case of a 26-year-old man with lymphangioma on the anterior dorsal part of the tongue, not associated with any dysfunction in mastication or speech disorders.